DEVELOPMENT OF CREATIVITY IN THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE PRACTICAL PSYCHOLOGISTS - Хоменко-Семенова, Леся Олексіївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article analyzes the essence of the technology of developing the creativity of future practical psychologists while studying the discipline «Psychology of advertising and public relations». The efficiency of the developed technology, which includes the systems of special tasks (tasks of creative character)ontheuseofICT, creation of situations close to the practicalproblemsis substantiated. It is indicated that the effectiveness of the developed technology consists of the creative interaction of students and a teacher, when training is not limitedby the mastering of rules and definitions, butisa process of acquiring knowledge when the student and a teacher become co-authors